Analisis Pengaruh Kompensasi dan Beban Kerja terhadap Kepuasan Kerja dan Turnover Intention pada Karyawan Inti Pangan, Kuningan - Lili Karmela Fitriani; Nina Yusiana (Universitas Kuningan, 2020)
Abstract This research was conducted at PT. Sumber Inti Pangan. This study aims to determine whether or not the influence of compensation and workload on employee turnover intention through job satisfaction as intervening variable.This study includes a type of comparative causal research with quantitative approach. Data collection methods in this study using questionnaires. Population in this research is employees of PT Sumber Inti Pangan with a sample of 129 respondents..Sampling technique used is propotional random sampling technique. The result showed that, Compensation has a significant effect on employee job satisfaction; Workload has a significant effect on employee job satisfaction; Job satisfaction has a significant effect on employee turnover intention; Compensation has no significant effect on employee turnover intention; Workload has a significant effect on employee turnover intention.Keywords : Compensation; Workload; Job Satisfaction; Turnover Intention.